A type of component (Insecta: Isoptera) hurt some of the architectural monuments, in Northern Vietnam and effective prevention and control - Ngo Xuan, Nam (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 3DO - 10.25073/2588-1140/vnunst.4522, 2017)
A survey of harmful components in some construction sites, 14101 sites in southern province of vietnam. The seven was found between, of which 4 species of insects are recognized as cultural relics including Coptotermes gestroi, Cryptotermes domesticus, Coptotermes ceylonicus và Odontotermes hainanensis. The final result showed that the processing efficiency of 98.6% to reach all varieties Nuisance in ruins, but only 72.59% average of all bond positions after the first treatment and 27 41% position effective treatment after 2nd treatment test results annually showed 97% of relics were treated termites termites not appear again.